1987
DOI: 10.1177/019262338701500203
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Effects of Vigabatrin on the Central Nervous System and Retina of Sprague Dawley and Lister-Hooded Rats

Abstract: Vigabatrin (gamma-vinyl GABA), an enzyme-activated, irreversible inhibitor of GABA transaminase, was administered orally to albino Sprague Dawley and pigmented Lister-Hooded rats. A dose-dependent retinal lesion characterized histologically by disruption of the outer nuclear layer was observed in the Sprague Dawley rat but not in Lister-Hooded rats, indicating that this alteration is related to the absence of pigment. The lesion is similar to that induced in albino rats by light and certain drugs. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
97
1
1

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 8 publications
14
97
1
1
Order By: Relevance
“…Our results extend the findings of Butler et al (27), who reported that systemic administration of VGB to Sprague-Dawley rats for 90 days produces retinotoxicity. Butler et al posited that light exposure might play a role in this subacute toxicity, but they did not investigate this possibility.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results extend the findings of Butler et al (27), who reported that systemic administration of VGB to Sprague-Dawley rats for 90 days produces retinotoxicity. Butler et al posited that light exposure might play a role in this subacute toxicity, but they did not investigate this possibility.…”
Section: Discussionsupporting
confidence: 92%
“…The damage to the outer retina we observed with brief systemic administration of VGB is similar to that observed with repeated systemic administration over a 90-day period (27). Although both brief and subacute systemic administration of VGB caused less damage than directly applying VGB to an isolated retina, the damage occurred in the outer retina in all cases.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In addition to routine assessment of paraffin-embedded sections, selected rats have been perfused for study by electron microscopy. These studies (Yarrington et al, 1985;Butler et al, 1987) show that the myelin vacuolation has resulted from separation of myelin lamellae at the intraperiod line, i.e., the membrane formed from fusion of the surface membranes of encircling oligodentrocyte cytoplasm. While identical intramyelinic oedema follows exposure to hexachlorophene (Towfighi et al, 1973), triethyltin (Aleu et al, 1963), and isoniazid (Carlton & Kreutzberg, 1966) (Butler et al, 1987 …”
Section: Rodent Studiesmentioning
confidence: 99%
“…Vigabatrin (y-vinyl GABA) is an enzyme-activated, irreversible, GABA-T inhibitor that has shown considerable promise in single and double-blind studies for the treatment seizure disorders in man (Gram et al, 1983;Rimmer & Richens, 1984;Browne et al, 1987). However, the clinical utility of this compound is potentially limited by the observation of microvacuolation within select CNS fibre tracts at high dose levels in the mouse, rat and dog (Yarrington et al, 1985; Butler et al, 1987).…”
Section: Introductionmentioning
confidence: 99%